Completely Recuperative Supercritical CO2 Recompression Brayton/Absorption Combined Power/Cooling Cycle: Performance Assessment and Optimization - Bing-Chuan Han; Yong-Dong Chen; Gai-Ge Yu; Xiao-Hong Wu; Tao-Tao Zhou (International Journal of Photoenergy)
Excessive heat losses and water consumption in cooling units are significant constraints restricting the application circumstances and performances for the SCO2 Brayton cycle, and the heat exchange capacity in the precooler (PRC) is typically 1.5 times that of power generation. Therefore, this research offers a high-integrated combined power/cooling system in which two waste heat exchangers (WHEs) and a rectifier (RET) are used instead of the PRC to achieve 100% exhaust heat recovery. Each component’s energy and exergy models are developed, and the operational characteristics, coupling relationships, and exergy destruction distribution are examined. Results indicate that, when compared to the Brayton cycle, the thermal and exergy efficiency is considerably increased, and the concentration difference and WHE1 pitch point difference have significant influences on system performance. Further exergoeconomic and optimization analysis reveals that the superior exergy case is mostly recommended for relevant thermal and exergy efficiency increasing rates of 13.7% and 9.17%, respectively, and the unit cost is 81.33% that of the base case. Turbine 1 (TUR1) and main compressor (MCP) are the first and second highest cost rates, respectively, and RET and generator (GEN) account for roughly 34% exergy destruction rate and 20% exergy destruction cost rate, respectively. In addition, reducing heat transfer differences in relevant equipment can further promote system performance.